Identifying Financial and Non-Financial Metrics Affecting Companies’ Sustainability Performance: A Thematic Analysis Approach - Karami, Mojgan; Ghiasvand, Alireza; Hematfar, Mahmoud (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The aim of this research is to identify financial and non-financial metrics that affect companies’ sustainability performance, which can be utilized to develop current financial reporting in order to provide comprehensive information on companies’ performance to assist in better decision-making. Method: The present study was conducted using the thematic analysis method and MAXQDA 2020 software. The research population consisted of experts (university faculty members, students, and doctoral graduates in finance, economics, accounting, and management), selected through snowball sampling. Data were collected through semi-structured interviews with experts until theoretical saturation was achieved. In this study, theoretical saturation was confirmed after conducting 26 interviews. Findings: In these interviews, experts suggested various financial and non-financial metrics in economic, social, and environmental dimensions for measuring and reporting companies’ sustainability performance. Economic metrics include sales growth, research and development, liquidity growth, financial leverage, company growth opportunities, industry competition, intangible assets, gross domestic product, company age, financial incentives, CEO duality, stock liquidity, board independence, corporate governance, ownership structure, company size, return on equity, economic value added, earnings per share, and return on assets. Social metrics include ethical conduct, job security for employees, and corporate social responsibility, while environmental metrics mentioned by most experts include waste and effluent management and clean (green) production. Conclusion: It can be concluded that considering globalization and attention to social and environmental issues and responsibilities alongside corporate profitability goals, and the necessity of considering stakeholders’ interests in the new corporate governance doctrine, reporting on companies’ sustainability performance is not only a need but a necessity for companies in the global competitive arena and as a strategic advantage.